The Effect of the Examples Non Examples Learning Model on the Active Learning of PAK of Class VIII Students of SMP Negeri 2 Lumbanjulu, Tobasa Regency, 2019/2020 Academic Year. - Darma Wati Pakpahan (IAKN Tarutung, 2020)
The research was to know the influence of the Non Examples Examples Learning Model on the Active Learning of Students of Class VIII of SMP Negeri 2 Lumbanjulu, 2019/2020. Research hypothesis is that there is an influence between the Examples non Examples Learning Model on the Active Learning of Students of Class VIII of SMP Negeri 2 Lumbanjulu, 2019/2020 Academic Year. The population is all students in SMP Negeri 2 Lumbanjulu totaling 115 people. Samples were taken 30% from 115 people = 40 people. This study concludes that the influence of the Examples non Examples Learning Model on the Active Learning of PAK of Class VIII Students of SMP Negeri 2 Lumbanjulu 2019/2020 is 32.9%.Keywords: Examples non Examples Learning Model, Student Learning Active Activity